Cover Image, Volume 1, Number 2, December 2019. Issue 2 (27th December 2019) - Shin, Woochul; Lu, Jun; Ji, Xiulei
Abstract : The electrolyte in Li‐S batteries has a chronic condition of "obesity, " and such batteries will not turn energetic unless the electrolyte gets lean. Nevertheless, the parsimonious use of electrolytes often fails to wet the cathode with a carbon surface. In article number 10.1002/cey2.10, Woochul Shin, Jun Lu and Xiulei Ji report that nano‐decorations of ZnS conjugate the electrolyte with the carbon‐surface of the sulfur cathode, thus creating a symbiotic interface for the high‐performing sulfur cathode.